Super-Multiple Deletion Analysis of Type III Effectors in Ralstonia solanacearum OE1-1 for Full Virulence Toward Host Plants - Lei, Ni; Chen, Li; Kiba, Akinori; Hikichi, Yasufumi; Zhang, Yong; Ohnishi, Kouhei (Frontiers in Microbiology, 2020)
Ralstonia solanacearum species complex (RSSC) posses extremely abundant type III effectors (T3Es) that are translocated into plant cells via a syringe-like apparatus assembled by a type III secretion system (T3SS) to subvert host defense initiated by innate immunity. More than 100 T3Es are predicted among different RSSC strains, with an average of about 70 T3Es in each strain. Among them, 32 T3Es are found to be conserved among the RSSC and hence called the core T3Es. Here, we genetically characterized contribution of abundant T3Es to virulence of a Japanese RSSC strain OE1-1 toward host plants. While all the T3Es members of AWR family contributed slightly to virulence, those of the GALA, HLK, and SKWP families did not influence full virulence of OE1-1. Mutant OE1-1D21E (with deletion of all 21 T3Es members of four families) exhibited slightly impaired virulence, while mutant OE1-1D36E (deleting all 21 T3Es of 4 families and 15 core T3Es) exhibited substantially reduced virulence. Mutant OE1-1D42E (deleting all 21 T3Es of 4 families, 15 core T3Es and 6 extended core T3Es) failed to cause any disease on tobacco plants with leaf infiltration but retained faint virulence on tobacco plants with petiole inoculation. The proliferation of mutant OE1-1D42E in tobacco stems was substantially impaired with about three orders of magnitude less than that of OE1-1, while no impact in tobacco leaves if directly infiltrated into leaves. On the contrary, the OE1-1D42E mutant retained faint virulence on eggplants with leaf infiltration but completely lost virulence on eggplants with root-cutting inoculation. The proliferation of OE1-1D42E mutant both in eggplant leaves and stems was substantially impaired. Intriguingly, mutant OE1-1D42E still caused necrotic lesions in tobacco and eggplant leaves, indicating that some other than the 42 removed effectors are involved in expansion of necrotic lesions in host leaves. All taken together, we here genetically demonstrated that all the core and extended core T3Es are nearly crucial for virulence of OE1-1 toward host plants and provided currently a kind of T3Es-free strain that enables primary functional studies of individual T3Es in host cells.